Hubungan Pengetahuan Remaja Tentang HIV/AIDS Dengan Perilaku Pencegahan HIV/AIDS - Kuswanti, Ina; Melina, Fitria; Mulaicin, Nafira (Jurnal Kesehatan Samodra Ilmu (JKSI), 2024)
Background: There are 36,902 cases of HIV and AIDS in Indonesia. The city of Yogyakarta ranks 1st as the province with the most HIV and AIDS sufferers. The number of HIV and AIDS cases was 206 in men and 89 in women, while those who were positive for AIDS were 36 in men and 13 in women. Most of the sufferers of HIV cases from 1993-2021 in DIY came from 1775 people aged 20-29 years, and 1701 people aged 30-39 years, 99 people aged 15-19 years. The most common HIV and AIDS risk factors found in DIY were 3152 heterosexuals, 1030 homosexuals and 287 injecting narcotics. Research Methods: This study used a cross-sectional method. The population in this study were all adolescents from SMA Piri I Yogyakarta, totaling 77 teenagers. The sampling technique in this study used accidental sampling with a sample of 41 respondents. The data analysis used was Univariate Analysis and Bivariate Analysis with the Kendall Tau statistical test. Research Results: The results of this study showed that the majority of adolescents' knowledge about HIV/AIDS was in the sufficient category, namely 19 people (46.3%), and the prevention behavior regarding HIV/AIDS was mostly in the good category, namely 34 (82.9%). Conclusion: Relationship between adolescent knowledge about HIV/AIDS and HIV/AIDS prevention behavior